Comparative Study of Behaviour of Soil and Soil-Bentonite Mixtures for The Construction of Impermeable Barriers - Martirosyan, Varsik; Yamukyan, Mihran (International Journal of Scientific Research in Civil Engineering, 2018)
The aim of the present work is to investigate the effect of admixture such as bentonite on the soil stabilization processes to determine its various characteristics and to develop a mix composition which can be economical for use as engineered impermeable barriers. Three types of the main soil materials differing grain size distribution mixed with various amount of sodium-bentonite as admixture (7.5%, 10.0% and 12.5% by soil dry weight) were used to study soil’s characteristics. It has been shown that the soil-bentonite mixtures’ permeability, plasticity and compaction characteristics are greatly affected by the type of main materials used in the mixtures. The plasticity index increased linearly with increasing amount of bentonite content and maximum dry density in compacted samples decreased linearly with increasing amount of bentonite content in all soil-bentonite mixtures. It was estimated that hydraulic conductivity of soil-bentonite mixtures decreased about two orders of magnitude only for Sample 2. Our data demonstrated that mixtures were suitable materials for barriers, because they met the statutory hydraulic conductivity requirement (i.e., k £ 1.0 · 10-8 m/s). Overall conclusion of this work is that improvements in the geotechnical properties of soil-bentonite mixtures depend on the amount of bentonite added and as well the type of main materials.
Keywords: Soil-Bentonite Mixture; Construction Materials; Impermeable Barriers; Permeability; Soil Stabilization